Applied Computation and Security Systems Volume Two - Chaki, Rituparna; Saeed, Khalid; Choudhury, Sankhayan; Chaki, Nabendu (Advances in Intelligent Systems and Computing,, 2015)
This book contains the extended version of the works that have been presented and discussed in the First International Doctoral Symposium on Applied Computation and Security Systems (ACSS 2014) held during April 18-20, 2014 in Kolkata, India. The symposium has been jointly organized by the AGH University of Science & Technology, Cracow, Poland and University of Calcutta, India. The Volume I of this double-volume book contains fourteen high quality book chapters in three different parts. Part 1 is on Pattern Recognition and it presents four chapters. Part 2 is on Imaging and Healthcare Applications contains four more book chapters. The Part 3 of this volume is on Wireless Sensor Networking and it includes as many as six chapters. Volume II of the book has three Parts presenting a total of eleven chapters in it. Part 4 consists of five excellent chapters on Software Engineering ranging from cloud service design to transactional memory. Part 5 in Volume II is on Cryptography with two book chapters in it. Part 6 of this volume is on Computer Aided Design with four chapters in it. We strongly believe that the twenty five chapters in these two volumes of Applied Computation and Security Systems will be appreciated by all its readers.